A Research Elective Course on Dietary Supplements to Engage Doctor of Pharmacy Students in Primary Literature Evaluation and Scholarly Activity. (December 2015) - Islam, Mohammed A.; Gunaseelan, Simi; Khan, Seher A.
Purpose: To develop and implement a research elective course to enhance skills of pharmacy students on primary literature evaluation and evidence-based practice on dietary supplements and generate scholarly publications. Methods: A 2 credit hour independent research elective course was designed and implemented in the third-year doctor of pharmacy curriculum. The course involved student-led research activities that included formulating research project, reviewing of primary literature, collection and evaluation of data, and writing of review articles for publication in peer-reviewed journals. An online survey was administered to evaluate students' perceptions of the course. Results: Students successfully completed the course. The course resulted in peer-reviewed publications through student–faculty collaboration. Pharmacy students enrolled in the elective course perceived that the course helped them enhance their analytical reasoning, critical thinking and drug-literature evaluation skills, gain evidence-based knowledge, and apply the knowledge into practice during their advanced pharmacy practice experiences community pharmacy rotations. Conclusions: The course provided opportunity to the pharmacy students to not only critically search and evaluate the literature but also publish in peer-reviewed journals. Other pharmacy schools/colleges can adopt this course model to create opportunities for student–faculty collaborations toward scholarly accomplishments.